Social reaction styles, interpersonal behaviors and person perception a multi-informant approach - Eronen, Sanna; Nurmi, Jari-Erik (Sage Publications, 1999)
Social strategies and reaction styles have been suggested to play an important role in initiating social relationships and in satisfaction with them. In order to investigate whether they are directly associated with popularity, unpopularity, lone-liness and evaluations about the social climate, or whether their impact is mediated by interpersonal behaviours and person perception, 92 students were asked to complete questionnaires measuring their social reaction styles, their lone-liness, the social climate in the class and their sociometric status. They also rated the behaviour of seven of their classmates, and these ratings were used as indices of social behaviour and person perception. The results showed that the impact of social reaction styles on popularity and unpopularity among classmates was mediated through social behaviour in particular, but also through person perception. However, social reaction styles were directly associated with feelings of loneliness and evaluation of the social climate. The results emphasize the importance of investigating social strategies and reaction styles as complex factors that include cognitive, behavioural and perceptual processes.